Role of Union Digital Centre (UDC) to Empower Rural People: A Case Study on Pabna Sadar Upazila, Bangladesh - Hosen, Md. Miraz; Nur, Sabia; Khatun, Mst. Nilufa (South Asian Journal of Social Sciences and Humanities, 2022)
Union Digital Centre (UDC) is a union based information service center and the purpose of which is to ensure information services at the doorsteps of grassroots people. The main purpose of this paper is to explore the role of UDC to empower the rural community as well as to find out the overall challenges of e-service delivery through UDC to the local citizens. Both the primary and the secondary data have been used to achieve the objectives of this study. The overall findings indicate that UDCs have the potential to empower the rural community but the study reveals that the poor section is very low in taking services from UDCs and the marginalized sections remain far behind from the empowerment goal as they lack engagement with the facilities provided through the UDCs. The paper also observed that, in spite of having some drawbacks, the beneficiaries have begun to realize the importance of UDCs which has emerged as a very effective strategy to empower those rural people. Since there does exist some challenges associated with e-services, it should be overcome as soon as possible. This paper also puts forward some recommendations in order to overcome the existing problem.